PENGAWASAN DAN EVALUASI PENDIDIKAN DALAM KONSEP AL-QUR’AN DAN HADIS - S.Pd.I, M.Pd, Khairul Husna, (Program Studi Pendidikan Agama Islam, 2017)
Monitoring and Evaluation of education based on the values ??of Islam as contained in the Koran and the Hadith as well as in the minds of the clergy and the practice of the history of the Islam.Dalam process, Islamic education makes an ideal destination as a target to be achieved in programs and products processed in Islamic education or educational output Islam. Actions and activities should be goal-oriented or a predetermined plan to determine the achievement of an objective evaluation of activities, namely. With the evaluation, then an activity can be known or determined tarap progress. Success or failure in achieving its goal of Islamic education can be seen after the evaluation of the output dihasilkannya.Untuk know the achievement of learning objectives or competencies expected by learners obtained through evaluation. In other words, the assessment or evaluation used as a tool to determine an educational purpose is achieved or not. Or to see the extent of student learning outcomes has reached its goal. In the evaluation of Islamic education is one component of the system of Islamic education should be done in a systematic and planned as a tool to measure the success or targets to be achieved in terms of Islamic education and the learning process in Government Elementary School Gampong Meutia Langsa.